2008
DOI: 10.1002/chin.200824041
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Reductive Acetylation of Carbonyl Compounds to Acetates with Pyridine Zinc Borohydride.

Abstract: Reduction O 0220Reductive Acetylation of Carbonyl Compounds to Acetates with Pyridine Zinc Borohydride. -The chemoselective one-pot reductive acetylation of a variety of carbonyl compounds is studied. Aldehydes react exclusively in the presence of ketones and the double bond in α,β-unsaturated carbonyl compounds remains unchanged. The advances of Zn(BH4)2(py) in comparison to other borohydride systems are discussed. -(ZEYNIZADEH*, B.; SETAMDIDEH, D.; FARAJI, F.; Bull. Korean Chem. Soc. 29 (2008) 1, 76-80; Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Treatment with catalytic Pd(OAc) 2 and PPh 3 worked reliably (5 g scale) and in high yield to give the enone 12 . Oxidative cleavage of the terminal alkene followed by immediate reduction of the aldehyde with freshly prepared zinc borohydride–pyridine complex11 gave the cyclopentanone 13 .…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with catalytic Pd(OAc) 2 and PPh 3 worked reliably (5 g scale) and in high yield to give the enone 12 . Oxidative cleavage of the terminal alkene followed by immediate reduction of the aldehyde with freshly prepared zinc borohydride–pyridine complex11 gave the cyclopentanone 13 .…”
Section: Methodsmentioning
confidence: 99%
“…Pyridine zinc borohydride was prepared by the reported procedure. 8 All reagents and substrates were purchased from Merck and Fluka companies with the best quality and they were used without further purification. IR and 1 H NMR spectra were recorded on Thermo Nicolet Nexus 670 FT-IR and 300 MHz Bruker Avance spectrometers, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11][12] In the course of our study to discover the new applications of this reagent, we found that the reduction of benzaldehyde with the reagent in ethyl acetate provided benzyl alcohol and benzyl acetate. Encouraged by the result, we undertook the study for one-pot reductive acetylation of a variety of carbonyl compounds, such as aldehydes, ketones and α,β-unsaturated enals/enones, to acetates using the reagent (Scheme 1).…”
Section: Introductionmentioning
confidence: 93%
“…1 Alternatively, reductive acylation is a simple method of obtaining acylated alcohols directly from ketones and aldehydes. 2,3 Such methods find utility in two distinct ways: (1) the synthesis of industrially useful or naturally occurring esters (e.g., polyesters or triglycerides, respectively), 4 or (2) the one-pot synthesis and protection of alcohols as synthetic intermediates (e.g., benzyl ester and acetyl groups). 5 Transforming carbonylcontaining compounds directly into acylated alcohols -as opposed to performing these tasks stepwise -improves the efficiency of multistep synthetic procedures by reducing the required time and energy, as well as the chemical waste produced.…”
mentioning
confidence: 99%
“…4 The more explored approach is the second one, using weak reducing agents such as NaBH 4 and ZnBH 4 in the presence of an ester, most commonly ethyl acetate that doubles as the solvent. 2,3,9,10,13 In the case of the first approach, there is a logistical hurdle to overcome. The most common and efficient way to form an ester directly from a carboxylic acid is via Fischer esterification.…”
mentioning
confidence: 99%